Uso de um manual didático com demonstrações experimentais simples para aulas de física - Farias, Bárbara Nicelle Maciel (Universidade Federal Rural do Semi-Árido, 2019)
It is known that classes with physical experiments can motivate and arouse the interest of basic education students in Science / Physics classes. However, for the teacher, it is increasingly difficult to include them in his planning. Physics teaching has been facing great challenges for a long time, such as lack of interest from students, lack of physical structure and materials in schools to prepare experimental classes, in addition to little pedagogical time in the classroom to perform them out. A viable option to reduce these limitations would be the insertion of classes with low cost experimental demonstrations. In this dissertation, the entire procedure for building and applying an educational product will be presented, titled Manual for Simple Experimental Demonstrations for Physics Classes, which aims to assist in the preparation of classes with demonstrative experiments using low-cost or recyclable materials, in order to arouse students' interest in Physics classes. The manual consists of 20 experimental demonstrations involving content from Mechanics to Electromagnetism, which can be carried out in parallel with the exposure of the content. Each demonstration presents the content covered within Physics, a brief theoretical foundation, the necessary material, illustrations and a proposal for use that involves some questions. It is not the intention of this product to provide ready-made teaching sequences or lesson plans, but rather to present an experimental demonstration that can be added to the teacher's lesson plan. The manual was used by physics teachers from public and private schools in the city of Aracati, freely, within their classes. The results were analyzed from the students' point of view through surveys and group discussions. Finally, it was concluded that the educational product contributed greatly to the students' interest in Physics classes and to the teaching and learning process, in addition to assisting in the planning of the Physics class with teachers
Keywords: Ensino de Física; Práticas Demonstrativas; Manual de Demonstrações; Physics Teaching; Demonstrative Practices; Demonstrations Manual; CIENCIAS EXATAS E DA TERRA::FISICA